A Certain Family for Higher-Order Derivatives of Multivalent Analytic Functions Associated with Dziok-Srivastava Operator - Abbas Kareem Wanas, Faiz Chaseb Khudher (Mathematical Statistician and Engineering Applications, 2023)
By making use of the principle of differential subordination, we introduce and study a family for higher-order derivatives of multivalent analytic functions which are defined by means of a Dziok-Srivastava operator. We obtain some important results connected to inclusion relationship, argument estimate, integral representation and subordination property.